A life cycle approach to Islamic wealth management and risk tolerance - Abdullah, Adam (IIUM Press, 2018)
This paper examines a holistic, life cycle approach to Islamic wealth planning and management in relation to risk tolerance. In determining asset allocation, Islamic wealth planning must consider more than the risk-return trade-off of financial assets and take into account life cycle financial advice. This paper adapts a life balance sheet accounting approach that reflects both explicit and implicit Shari’ah compliant items in determining core capital, non-discretionary and discretionary wealth. The significance is that a Muslim wealth manager can objectively determine risk tolerance from implied leverage within the discretionary wealth framework of life cycle financial advice that better reflects the private client’s emotional goals and provides more flexibility in asset allocation. This contrasts with traditional net worth analysis of product-orientated personal financial planning that includes a subjective risk tolerance function derived from a questionnaire in determining asset allocation. This paper proposes a more holistic, sophisticated, goal-orientated approach, thereby enhancing the delivery of Shari’ah compliant Islamic wealth management services.